2004
DOI: 10.2176/nmc.44.509
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Hemodynamic Measurements of the Vertebral Artery and Common Carotid Artery

Abstract: The hemodynamics in the vertebrobasilar artery (VBA) system were investigated in patients with vertebrobasilar insufficiency (VBI). Vertebral artery (VA) stump pressure and blood flows in the VA and common carotid artery (CCA) were intraoperatively measured in 45 patients who underwent surgical correction of the first segment of the VA (V 1 ) for angiographic tortuosity, kinking, and/or stenosis manifesting as symptomatic VBI. The effects of changes in the systemic arterial blood pressure (SABP) induced by tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In 2008, Cassaglia, Griffiths, and Walker showed that sympathetic nerve activity withdraws the blood flow while sympathectomy can increase it, and other experiments also confirmed this theory. 14 16 Miyoshi also investigated sympathetic and parasympathetic changes produced by the stimulation of nerves around the proximal vertebral artery (the vertebral nerve) in a cat model, and found that pupillary changes, pulse, and blood pressure changes in cats. 17 This suggests that sympathetic excitation can produce a decrease in blood flow of the vertebral artery.…”
Section: Discussionmentioning
confidence: 99%
“…In 2008, Cassaglia, Griffiths, and Walker showed that sympathetic nerve activity withdraws the blood flow while sympathectomy can increase it, and other experiments also confirmed this theory. 14 16 Miyoshi also investigated sympathetic and parasympathetic changes produced by the stimulation of nerves around the proximal vertebral artery (the vertebral nerve) in a cat model, and found that pupillary changes, pulse, and blood pressure changes in cats. 17 This suggests that sympathetic excitation can produce a decrease in blood flow of the vertebral artery.…”
Section: Discussionmentioning
confidence: 99%